(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
There are a lot of extremely gifted and talented Indians who sacrificed their very promising and rewarding lives for their ultimate reward, freeing their motherland from the chains of bondage. Sarat Chandra Chattopadhyay, celebrated author, poet and social reformer is a stellar name amongst those who have our abiding respect and reverence. The paper talks about his work in the Howrah district of West Bengal during the peak of the freedom struggle in detail.